Soil Suitability Analysis for Crop Planning in Kheragarah Tehsil of Agra District, Uttar Pradesh - A. Sarangi; A.K. Mishra, A.A. Mustafa, Man Singh, Nayan Ahmed R.N Sahoo, Manoj Khanna (Journal of the Indian Society of Soil Science, 2017)
Soil suitability is prerequisite for sustainable agriculture and it plays a pivotal role in crop production especially in degraded lands. In this study, an attempt was made to assess the soil suitability of Kheragarah tehsil for production of major crops during rabi and kharif seasons. Six pedons of the tehsil were studied for their physical and chemical properties and their suitability for growing wheat, maize, cotton and barley. All pedons were found to be moderate to deep in soil depth, well to poorly drained, slightly to strongly alkaline (pH 7.98 - 9.43), slightly to highly saline (ECe 1.81- 7.23 dS m-1), low in organic carbon (1.1-2.7 g kg-1), CEC medium to high [19.7 - 24.4 cmol(p+) kg-1]. The calcium carbonate content ranged from nil to 14.3%. Soils were low in available N (72.0 to 220.0 kg ha-1), low to high in available P (3.7–15.0 kg ha-1) and medium to high in available K (153.0 - 361.6 kg ha-1). However, the soils were adequate in available Fe and Mn but low in available Zn and Cu content. The soil suitability analysis revealed that soils at P1 locations were moderately suitable for growing wheat and barley and marginally suitable for cotton and maize cultivations. The P2 soils were moderately suitable for wheat, maize and barley and marginally suitable for cotton. However, the soils of P3 and P5 were not suitable for growing any of the selected crops. But, P6 soils were moderately suitable for growing all selected crops whereas, P4 soils were highly suitable for all selected crops except maize.